Faculty Information Systems Project Management: A Comparison of CPM And PERT Methods - Gustian Rama Putra; Reza Ariftiarno; Lita Karlitasari; Dinar Munggaran Akhmad (Komputasi: Jurnal Ilmiah Ilmu Komputer dan Matematika, 2025)
This research evaluates the Critical Path Method (CPM) and the Program Evaluation and Review Technique (PERT) to determine the most efficient scheduling method for the development of an information system at the Faculty of Economics and Business, Universitas Pakuan. The system aims to consolidate work unit information and assist faculty leaders in decision-making. Both methods identified the same critical path (A-B-C-E-G-H), ensuring focus on activities critical to project completion. The CPM method estimated a project duration of 50 days, while the PERT method estimated 52 days. The two-day difference reflects CPM’s deterministic and optimistic approach, making it suitable for projects with predictable timelines. PERT, with its probabilistic calculations, incorporates activity duration variations and risks, providing more conservative estimates for projects with higher uncertainty. Due to its shorter duration and potential cost savings, the CPM method is recommended for the Faculty's information system development project. This research emphasizes the importance of selecting a scheduling method aligned with project complexity and uncertainty.